The concept of knowledge from Islam perspective - Shogar, Ibrahim (2019)
For a meaningful life human needs three types of knowledge: 1. Knowledge of the metaphysical world to answer the fundamental questions and form the worldview, to give meaning to life, to build philosophy / framework for his acts. 2. Knowledge of the physical world: to interpret the natural events correctly, to deal with things proper (relating between cause and effect), and to fulfill his material needs; and 3. Knowledge of principles of right conduct (values): to manage / change yourself, to manage / change your community (to maintain justice, peace, harmony, and tranquility for all), to deal with all creatures ethically. We gain the second mode of knowledge (physical world) through science; We learn the first and third modes of knowledge (metaphysical and right conduct) through reason and religion. Therefore, integration of science and religion is important.